2022
DOI: 10.1187/cbe.21-09-0229
|View full text |Cite
|
Sign up to set email alerts
|

Community College Student Understanding and Perceptions of Evolution

Abstract: A comparison of university and community college students’ evolution education variables revealed evidence of similarities and differences between populations. Community college students perceived more conflict between their religions and evolution, and their understanding of evolution was less associated with acceptance compared with university students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…In addition, researchers have found that students with creationist views can demonstrate a solid understanding of evolution and students who identify themselves as evolutionists may in turn demonstrate a poor understanding of evolutionary theory (Demastes-Southerland et al 1995;Hermann 2016). Another study also showed that understanding and acceptance can be related to each other in some college students but less so in others (Barnes et al 2022). It is, however, unclear exactly how knowledge and acceptance influence each other (Dunk et al 2019).…”
Section: Significancementioning
confidence: 98%
See 1 more Smart Citation
“…In addition, researchers have found that students with creationist views can demonstrate a solid understanding of evolution and students who identify themselves as evolutionists may in turn demonstrate a poor understanding of evolutionary theory (Demastes-Southerland et al 1995;Hermann 2016). Another study also showed that understanding and acceptance can be related to each other in some college students but less so in others (Barnes et al 2022). It is, however, unclear exactly how knowledge and acceptance influence each other (Dunk et al 2019).…”
Section: Significancementioning
confidence: 98%
“…Using university student population samples and generalizing their results to the general population is problematic (Hanel and Vione 2016). Specifically, in regard to evolution understanding, students enrolled in community college have reported lower levels of understanding than those enrolled in a four-year university (Barnes et al 2022). It may be that community college students are more representative of the general public than fouryear college students as they are often representative of a broader range of ages.…”
Section: Significancementioning
confidence: 99%
“…Moreover, acceptance of micro‐evolution and macro‐evolution are highly correlated (Nadelson & Southerland, 2012). For community college students, however, acceptance of micro‐evolution was predicted by understanding of evolution, but not for macro‐evolution (Barnes et al, 2022). In contrast, for university students, both types of acceptance were predicted by understanding (Barnes et al, 2022) as well as trust in science (Nadelson & Hardy, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For community college students, however, acceptance of micro‐evolution was predicted by understanding of evolution, but not for macro‐evolution (Barnes et al, 2022). In contrast, for university students, both types of acceptance were predicted by understanding (Barnes et al, 2022) as well as trust in science (Nadelson & Hardy, 2015). Combined with the findings from our study, it seems that there may be differences in understanding of micro‐ and macro‐evolutionary processes and more subtle differences in acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the usage of the I‐SEA has increased (e.g., Barnes et al, 2019, 2020a, 2020b, 2021a, 2021b, 2022b; Ferguson & Jensen, 2021; Fiedler et al, 2019; Hartelt et al, 2022; Rachmatullah et al, 2018; Romine et al, 2018; Sbeglia & Nehm, 2019, 2020; Wingert et al, 2022), and several new insights into the structure of the scales were presented. For example, Sbeglia and Nehm (2019) found that the scales for microevolution and macroevolution are very stable within a university student sample, while the human evolution scale may be split into two sub‐dimensions (i.e., human microevolution and human macroevolution).…”
Section: Measuring Evolution Acceptancementioning
confidence: 99%